Tradition in the Novels of Anwar Ridhwan and Putu Wijaya (Malay Literature, 2011)
This paper is the result of a comparative study carried out on the novels of Anwar Ridhwan and Putu Wijaya, writers who represent Malaysian and Indonesian authorship respectively. This study focuses on the inclination of both writers to dignify "tradition" in their work. What is meant by the framework of "tradition" is that both writers source their materials mainly from traditional texts in order to construct the structure of the novels which is the object of our attention. Specifically, the novel Hari-hari Terakhir Seorang Seniman (Anwar Ridhwan) makes references to the romance Si Gembang or Teluk Bidung Kota Lama while the novel Perang (Putu Wijaya), to the classical text the Mahabharata. Aside that, "tradition" as is presented by the writers in the novels under study, has been identified to take account of the concept of tradition which is the authorship ideology of both writers - Anwar Ridhwan with his concept kampung halaman Melayu (Malay hometown), Putu Wijaya with his concept desa-kala-patra (found in the Balinese tradition). These "traditions" are anchored in their experimental works which apear to be defying convention; a predilection that clearly is in line with the authorial rhythm of these outstanding writers. The study conducted employs the intertextual framework as well as dialogism advanced by Mikhail Bakhtin and Julia Kristeva; a framework for observing authorship processes that is directed towards the effectiveness of creation theory. The study finds that both writers conform to the cultural traditions of their people, are clearly appreciative of these traditions, perfom meaning inversions in the novels examined (the hypertext) which are not evident in the pre-existing text (the hypotext).Keywords: Anwar Ridhwan, Putu Wijaya, the novel Hari-hari Terakhir Seorang Seniman, the novel Perang, intertextuality, tradition.